A Systematic Review of Knowledge and Perception Regarding Generic Medicines Among Indonesians - Pandanwangi TW, Siti; Agustina, Diana; Karsidin, Bambang (Journal La Medihealtico, 2024)
Generic medicines are a type of medicine with an official name that has been assigned to the efficacious substance it contains. Generic medicines have the same effectiveness as patented medicines. Many people think that generic medicines are of low quality, so they prefer branded generic medicines or patented medicines. This systematic review aims to report the results of a search for previously reviewed studies that focus on the level of public knowledge and perception of generic medicines. The research method used is a literature study method using journal data from the last 10 years. Journal collection was carried out by searching online journal databases indexed in Google Scholar, and PubMed using Mesh (Medical Subject Headings) with a focus on the keywords "knowledge", "perception", and "generic medicines". The results of this research are that the level of Indonesian people's knowledge of generic medicines is quite good but not evenly distributed, especially among groups of people who have a strong belief that cheap medicines are of lower quality. Acceptance of generic medicines tends to be higher in communities with higher levels of education. Communities with low socio-economic conditions generally have a low level of education so they tend to have greater distrust of generic medicines. This research concludes that it is important to provide information about generic medicines aggressively and continuously to the public to increase public trust in generic medicines. In addition, prescribing generic medicines by physicians is the main thing to eliminate public distrust about generic medicines.